A Robust Threshold for Iterative Channel Estimation in OFDM Systems - Kalaycioglu, Aykut; Ilk, H. Goekhan (Společnost pro radioelektronické inženýrství, 2010)
A novel threshold computation method for pilot symbol assisted iterative channel estimation in OFDM systems is considered. As the bits are transmitted in packets, the proposed technique is based on calculating a particular threshold for each data packet in order to select the reliable decoder output symbols to improve the channel estimation performance. Iteratively, additional pilot symbols are established according to the threshold and the channel is re-estimated with the new pilots inserted to the known channel estimation pilot set. The proposed threshold calculation method for selecting additional pilots performs better than non-iterative channel estimation, no threshold and fixed threshold techniques in poor HF channel simulations.
Keywords: Adaptive threshold; additional pilot symbols; error correction decoder; soft outputs; HF